MAQUILA & MAQUILADORA - Wong Torres, Zelma (2010)
The maquila and maquiladora must be addressed as a problem that professionals must understand and participate extensively to help the poor rise above that level, because firms under this system are systematically appropriating emerging countries, justified that do not have education, health, no job, considering the pittance they give us is more than enough for all of us. It is necessary for Peruvian professionals look to our country as powerful it is, who failed so far to open their eyes and recognize the wealth they have, here is to remember the words of Don Antonio Raimondi “Peru is a beggar sitting on a bench of gold today is just like waking up and being discovered, entrepreneurs are betting that we should not awaken, we must not let them because then Peruvian brother, understand that the wealthy businessman takes advantage of our ignorance and our poverty to be useful fools do not know how to defend and exploit what we have in our own benefit, both now and in the future for our generations to come. We must show our real professional competence that we no longer operating as they have always been big business, we require 50% of all profits to be distributed to workers, the solution we have formed joint uniting and make our opinions and ideas that will improve analyzed and displayed among ourselves.